Relationship between the innovation and competitiveness - Lădaru Georgiana, Raluca; Romanescu, Doiniţa; Rusescu, Marius (Economics of Agriculture, 2010)
This paper is written in order to shed light on the complex relationship between the innovation and competitiveness. Innovation is the end of a supply process, know-how and processing. It is also the beginning of an exploitation process, which may lead to improve the frm performance, namely its competitiveness. This recursive process of knowledge supply, processing and exploitation includes the value chain innovation. In the operation phase, innovation both in the products and in the process, contribute positively on the company performance.